A new species of the genus Neosilba (Diptera: Lonchaeidae) - Strikis, P.c.; Prado, A.p. (Zootaxa, 2005)
A new species of the genus Neosilba McAlpine (Lonchaeidae) is described. This genus has a wide distribution in the Neotropical region and some of its species are considered to be fruit pests, in addition to fruit flies of the family Tephritidae. This genus is also known to have a cryptic complex of species, which makes species belonging to this genus difficult to identify. .